Phylogenomics With Hyb-Seq Unravels Korean Hosta Evolution - Yoo, Mi-Jeong; Lee, Byoung-Yoon; Kim, Sangtae; Lim, Chae Eun (Frontiers in Plant Science, 2021)
The genus Hosta (Agavoideae; Asparagaceae) is one of the most popular landscaping and ornamental plants native to temperate East Asia. Their popularity has led to extensive hybridization to develop various cultivars. However, their long history of hybridization, cultivation, and selection has brought about taxonomic confusion in the Hosta species delimitation along with their indistinguishable morphology. Here, we conducted the first broad phylogenetic analyses of Hosta species based on the most comprehensive genomic data. To do so, we captured 246 nuclear gene sequences and plastid genomes from 55 accessions of Korean Hosta species using the Hyb-Seq method. As a result, this study provides the following novel and significant findings: 1) Phylogenetic analyses of the captured sequences retrieved six species groups of Hosta in Korea compared to five to eleven species based on the previous studies, 2) their phylogenetic relationships suggested that the large genome size was ancestral and the diversification of Korean Hosta species was accompanied by decreases in genome sizes, 3) comparison between nuclear genes and plastome revealed several introgressive hybridization events between Hosta species, and 4) divergence time estimated here showed that Hosta lineage diverged 35.59 million years ago, while Korean Hosta species rapidly diversified during the late Miocene. Last, we explored the possibility of these genomic data for inferring the origin of cultivated species. In summary, this study provides the most comprehensive genomic resources to be used in phylogenetic analysis, the development of potential molecular markers for the population and conservation studies of Hosta, as well as unraveling the origin of many cultivar species.